Impact of educational services quality on student satisfaction, image, and student loyalty - Fahlevi, Agam Aulia; Sugiat, Maria Apsari (Indonesian Research Journal in Education |IRJE|, 2025)
This research analyzes how the quality of education services influences student satisfaction, image, and loyalty. All respondents are students of a public senior high school Sumatera Selatan. Student satisfaction is a preference in the subjective evaluation of the entire experience associated with the educational process. Image means the perception of the service provided to the student, consisting of cognitive and communicative perceptions. Loyal students can positively impact learning quality through participation and committed behaviour. In this research, a quantitative method was utilized. The method used was quantitative, with data collection techniques using a questionnaire instrument filled in directly by respondents online and processed using the SEM PLS. The variables of academic and non-academic aspects had a positive but insignificant effect on student satisfaction. On the other hand, program issues, reputation, and access positively and significantly affected student satisfaction. The relationship between the quality of school education services, student satisfaction, school image, and student loyalty, among others, is important to clarify the limitations of this research and serve as a guide for future research.